A Case of Incomplete Central Retinal Artery Occlusion Associated with Short Posterior Ciliary Artery Occlusion - Shinji Makino; Mikiko Takezawa; Yukihiro Sato (Case Reports in Ophthalmological Medicine, 2013)
To our knowledge, incomplete central retinal artery occlusion associated with short posterior ciliary artery occlusion is extremely rare. Herein, we describe a case of a 62-year-old man who was referred to our hospital with of transient blindness in his right eye. At initial examination, the patient’s best-corrected visual acuity was 18/20 in the right eye. Fundus examination showed multiple soft exudates around the optic disc and mild macular retinal edema in his right eye; however, a cherry red spot on the macula was not detected. Fluorescein angiography revealed delayed dye inflow into the nasal choroidal hemisphere that is supplied by the short posterior ciliary artery. The following day, the patient’s visual acuity improved to 20/20. Soft exudates around the optic disc increased during observation and gradually disappeared. His hemodynamic parameters revealed subclavian steal syndrome as examined by cervical ultrasonography and digital subtraction angiography. We speculate that his transient blindness was due to ophthalmic artery spasms. In this particular case, spasms of the ophthalmic artery and occlusion of the short posterior ciliary artery occurred simultaneously. As the short posterior ciliary artery branches from the ophthalmic artery, the anatomical location of the lesion might be near the branching of both arteries.